“Peach Gum Dessert” Investment Feasibility Analysis - Bernadine Bernadine; Brastoro Brastoro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to determine the feasibility of Investment in Peach Gum dessert for five years, 2022-2026. The sample of this study is determined based on data and information from the company's financial statements, in the form of a Balance Sheet, Cash Flow Statement, and Profit and Loss Statements for the 2022 -2026 period. The data analysis technique uses investment feasibility methods, namely Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The results showed that the investment in Peach Gum dessert is feasible because, based on the Income Statement Performance for the next five years, it generates an increasing profit every year. Moreover, based on Cash Flow Performance for the next five years, the final cash flow is always positive and increases yearly. While the results of the calculation using the investment feasibility assessment resulted in an NPV of Rp. 708.689.398, Internal Rate of Return (IRR) of 40%, where this value is greater than the expected rate of return of 7,68%, Profitability Index (PI) of 2,3158349625 with a total payback period of 2 years six months 15 days, so it can be concluded that the investment is feasible.